1999
DOI: 10.1177/107110079902000210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ankle and Knee Position on Tension in the Achilles Tendon

Abstract: The purpose of this study was to evaluate the relative contributions of ankle and knee position to tension in the Achilles tendon and to determine whether there exists a position of plantarflexion at which the passive tensioning effect of knee extension is eliminated. Seven matched pairs of fresh-frozen cadaver lower extremities were tested. A buckle transducer was used to measure forces in the tendon throughout the full range of knee motion, with the hindfoot fixed. Positioning the hindfoot in 20 degrees to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 5 publications
3
26
0
Order By: Relevance
“…Thus, PF of the ankle alone appears to loosen the Achilles-tendon complex, and any further loosening produced by flexing the knee may not have resulted in any additional effect. This finding is supported by Davis et al, 20 who measured the passive tension forces in the Achilles tendon at various knee and ankle positions and reported that positioning the hindfoot in at least 156 of PF effectively eliminated tension in the Achilles tendon. When examined with the knee in full extension, tension within the Achilles tendon was eliminated at 306 of PF.…”
Section: Effects Of Knee Positioningsupporting
confidence: 75%
See 2 more Smart Citations
“…Thus, PF of the ankle alone appears to loosen the Achilles-tendon complex, and any further loosening produced by flexing the knee may not have resulted in any additional effect. This finding is supported by Davis et al, 20 who measured the passive tension forces in the Achilles tendon at various knee and ankle positions and reported that positioning the hindfoot in at least 156 of PF effectively eliminated tension in the Achilles tendon. When examined with the knee in full extension, tension within the Achilles tendon was eliminated at 306 of PF.…”
Section: Effects Of Knee Positioningsupporting
confidence: 75%
“…When examined with the knee in full extension, tension within the Achilles tendon was eliminated at 306 of PF. 20 …”
Section: Effects Of Knee Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…The soleus muscle has a stabilizing effect on the foot and is continuously active during erect standing (Norkin and Levangie, 1983). Various positions of the knee and ankle joints can affect the forces along the Achilles tendon (Arndt et al, 1998, Davis et al, 1999. The Achilles tendon is broad and flat where it originates and becomes more narrow and rounded distally before it fans out at the insertion (Józsa and Kannus, 1997).…”
Section: Anatomymentioning
confidence: 99%
“…On the other hand, Davis et al [26] stated that positioning the hindfoot in 20-25 degrees of plantarflexion effectively eliminates tension in the Achilles tendon, regardless of knee position.…”
Section: Discussionmentioning
confidence: 99%